Inguinal abscess following Trans-abdominal Preperitoneal Mesh repair for inguinal hernia - Nakarmi, Rajiv; Shrestha, Muza; Maharjan, Sundar (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Laparoscopic hernia surgery is performed by almost every general and laparoscopic surgeon worldwide, Trans-abdominal Preperitoneal (TAPP) and Totally Extraperitoneal (TEP) being the most frequently performed. Seroma formation leading to deep seated mesh infection with abscess is rare but once it occurs it can be very difficult to treat. The rate of mesh infection after open mesh repair is reported to be between 0.5% - 3%, whereas in laparoscopic repair is less than 0.16%. Seroma formation following TAPP is 3%-8% and following TEP is 0.5-12.2%. Case Report: A 19 years old male presented with groin swelling, fever and weight loss three months after the laparoscopic TAPP surgery for right inguinal hernia. Workup showed he had developed mesh infection with pre-peritoneal abscess which was managed with open drainage of the abscess with removal of the infected mesh. Conclusion: Seroma formation may result in abscess formation. If occurred removal of the mesh with drainage of abscess is often required. The chance of recurrence of hernia following management of infected mesh should always be considered